VO#031 Proposal of facade curtain wall & relative works rev.0 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of proposal for facade curtain wall & relative works of BRACU new campus project.